THE EFFECT OF DIFFERENT PRETANNING INGREDIENTS ON QUALITY OF THE SKIN OF TILAPIA FISH(OREOCHROMIS NILOTICUS) TANNED OF GAMBIER (UNCARIA GAMBIER) - Heru Susanto; Swatika Juhana; Fadzkurisma Robbika; Fauzi Ashari; Wahyu Fajar Winata (Politek ATK Yogyakarta Press, 2024)
Tanning of tilapia fish skin (Oreochromis niloticus) has been carried out using a variety of pretanning materials such as aluminum, chrome, glutaraldehyde, syntan with gambier (Uncaria gambier) as the main tanning agent. The research aims to determine the effect of pretanning ingredients on the physical and chemical quality of the skin tilapia fish of gambir so that the best formulation can be obtained. The process of tanning tilapia skin is carried out conventionally from salt-cured tilapia skin processed by BHO to the pikling process, pretanning with a variety of pretanning materials chrome, aluminum, glutaraldehyde and SB sodatan at 4% each, followed by main tanning with gambier various (25% 30%, 35%), post tanning, and finishing. The results of the skin quality test of tilapia fish tanned gambier with the best formula, namely code L with SB 4% sodatan pretanning with 35% gambier. This optimum formula produces a shrinkage temperature of 70 oC, higher tensile strength, sewing strength and burst resistance, the highest bound tannin content is 30.87%, and the degree of tanning is 69.18%.